Avian Fauna Diversity of Lungh Lake Sanctuary Sindh, Pakistan - Sahibzado Farmanullah Rashdi; Kalsoom shaikh; Ali Raza Soomro; Khadim Hussain Memon; Noshaba Zaheer Khan; Irfan Ali Tagar (Dialogue Social Science Review (DSSR), 2025)
The full-flowered Lungh Lake Sanctuary is known for its diverse range of birds. According to the current study, many bird species can be found in wetlands. Although we learned about a wide range of bird species there, 53 distinct bird species were identified during fieldwork. These birds were divided into 10 families, including the Ardeidae, Rallidae, Charadridae, Alcedinidae, Sturnidae, Muscicapidae, Columbidae, Cuculidae, Anatidae, Recurvirostridae, and Passeridae. The Charadridae and Sturnidae were smaller in number, whereas the Anatidae were a large family with fame. It was observed that some of the families were residents and that many were tourists. Except for the Passeridae and Columbidae families, these species mainly depend on water. Some of the birds included in this study were insects and grain eaters, but most of the birds subjected to this study were fish eaters.